Overexpression of TPD52L2 in HNSCC: prognostic significance and correlation with immune infiltrates - Min Lu; Haoyu Xia; Jing Xu; Zijun Liao; Yuwen Li; Hanwei Peng (BMC, 2024)
Abstract Background Evidence has been presented that the tumor protein D52 (TPD52) family plays a critical role in tumor development and progression. As a member of the TPD52 family, the changes in TPD52L2 gene status are instrumental in kinds of cancer development. However, its effects on patient prognosis and immune infiltration in Head and Neck Squamous Carcinoma (HNSCC) are still poorly understood. Methods The Tumor Genome Atlas (TCGA), Gene Expression Omnibus (GEO), and c-BioPortal database was used to explore the expression pattern, prognostic value, and variation of gene status in HNSCC. The LinkedOmics database was used to obtain the co-expression genes of TPD52L2 and identify the diagnostic value of TPD52L2 in HNSCC. The correlations between TPD52L2 expression and six main types of immune cell infiltrations and immune signatures were explored using Tumor Immune Estimation Resource (TIMER). The correlation between TPD52L2 expression and immune checkpoint genes (ICGs) was analyzed by TCGA database. Immunohistochemistry (IHC) was performed to validate the expression of three ICGs (PDL1, PDL2, EGFR) and TPD52L2 using 5 paired HNSCC and normal head and neck tissues. Polymerase Chain Reaction (PCR) and Western Blot (WB) of HNSCC and normal head and neck cell lines were performed to verify the high level of TPD52L2 mRNA and protein expression. protein expression of TPD52L2 in pan-cancer was also validated using UALCAN. Results TPD52L2 was overexpressed in tumor tissues, and it predicted worse survival status in HNSCC. ROC analysis suggested that TPD52L2 had a diagnostic value. Multivariate Cox analysis identified TPD52L2 as an independent negative prognostic marker of overall survival. Functional network analysis suggested that TPD52L2 was associated with immune-related signaling pathways, cell migration pathways, and cancer-related pathways. High expression of TPD52L2 was associated with a more mutant frequency of TP53. Notably, we found that the expression of TPD52L2 was closely negatively correlated with the infiltration levels of 15 types of immune cells and positively correlated with several immune markers. PCR, WB experiments, and UALCAN database verified the high level of TPD52L2 mRNA and protein expression. Conclusion TPD52L2 is upregulated in HNSCC, which is an independent factor for adverse prognosis prediction. It probably plays a role in the negative regulation of immune cell infiltration. TPD52L2 might be a promising prognostic biomarker and therapeutic target in HNSCC.